2006
DOI: 10.1016/j.msea.2006.03.100
|View full text |Cite
|
Sign up to set email alerts
|

Texture characterisation of hexagonal metals: Magnesium AZ91 alloy, welded by laser processing

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. ABSTRACTThe objective was to study the mechanical properties of a magnesium alloy welded by a CO 2 laser. Residual stresses were measured by X-ray diffraction. They were calculated by the classic sin 2 Ψ method in the isotropic zones by using the orientation distribution function

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…The micro hardness decreases slightly in the fusion zone and in the TMAZ (82 ± 2 HV); the slight decrease in the HAZ, where the grain sizes are identical to those in the BM, can be explained by the fact the material has been submitted to a thermal annealing cycle [6,8]. In the welded zone there is a slight reduction in micro hardness despite the fact that the grain size is greatly reduced; the values obtained do not obey the Hall and Petch Law [10]. Within the welded zone the variation of micro hardness can be explained by the fact that the high degree plastic deformation and heating are conducive to the phenomenon of dynamic recrystallization resulting from dynamic recovery.…”
Section: Evolution Of Micro-hardnessmentioning
confidence: 88%
See 3 more Smart Citations
“…The micro hardness decreases slightly in the fusion zone and in the TMAZ (82 ± 2 HV); the slight decrease in the HAZ, where the grain sizes are identical to those in the BM, can be explained by the fact the material has been submitted to a thermal annealing cycle [6,8]. In the welded zone there is a slight reduction in micro hardness despite the fact that the grain size is greatly reduced; the values obtained do not obey the Hall and Petch Law [10]. Within the welded zone the variation of micro hardness can be explained by the fact that the high degree plastic deformation and heating are conducive to the phenomenon of dynamic recrystallization resulting from dynamic recovery.…”
Section: Evolution Of Micro-hardnessmentioning
confidence: 88%
“…Table 1 shows the chemical specification of the AZ31 magnesium alloy supplied. [10] AZ31 magnesium alloys used were rolled to produce 2 mm thin plates from 100 mm ingots which were hot rolled with several passes using a 4 rollers Quarto rolling mill. Strain rates between 5-20% (thickness reduction per pass) and rolling speeds between 0.5-2 m/s were used.…”
Section: Sample Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that for thin AZ31 plates (1, 8 mm), a 1.5 kW beam power was sufficient for achieving full penetration. In our experiences, for achieving full penetration, 3 mm AZ91 plates welds were produced at 4 kW (Kouadri & Barrallier, 2006).…”
Section: Penetration Depth (Mm)mentioning
confidence: 99%